Kinetic and structural investigation of the cytokinin oxidase/dehydrogenase active site - Kopečný, David; Končitíková, Radka; Popelka, Hana; Briozzo, Pierre; Vigouroux, Armelle; Kopečná, Martina; Zalabák, David; Šebela, Marek; Skopalová, Jana; Frébort, Ivo; Moréra, Solange (The FEBS journal, 2016)
Cytokinins are hormones that regulate plant development and their environmental responses. Their levels are mainly controlled by the cytokinin oxidase/dehydrogenase (CKO), which oxidatively cleaves cytokinins using redox-active electron acceptors. CKO belongs to the group of flavoproteins with an 8α-N1-histidyl FAD covalent linkage. Here, we investigated the role of seven active site residues, H105, D169, E288, V378, E381, P427 and L492, in substrate binding and catalysis of the CKO1 from maize (Zea mays, ZmCKO1) combining site-directed mutagenesis with kinetics and X-ray crystallography. We identify E381 as a key residue for enzyme specificity that restricts substrate binding as well as quinone electron acceptor binding. We show that D169 is important for catalysis and that H105 covalently linked to FAD maintains the enzyme's structural integrity, stability and high rates with electron acceptors. The L492A mutation significantly modulates the cleavage of aromatic cytokinins and zeatin isomers. The high resolution X-ray structures of ZmCKO1 and the E381S variant in complex with N6-(2-isopentenyl)adenosine reveal the binding mode of cytokinin ribosides. Those of ZmCKO2 and ZmCKO4a contain a mobile domain, which might contribute to binding of the N9 substituted cytokinins.
Keywords: Zea mays; Cytokinins; Catalytic Domain; Flavin-Adenine Dinucleotide; Substrate Specificity; maize; Protein Conformation; krystalografie rentgenová; kukuřice setá; flavinadenindinukleotid; Crystallography, X-Ray; plant hormone; mutageneze cílená; oxidoreduktasy; Kinetics; flavoprotein; substrátová specifita; katalytická doména; site-directed mutagenesis; cytokinin oxidase/dehydrogenase; Mutagenesis, Site-Directed; crystal structure; Oxidoreductases; cytokininy; kinetika; konformace proteinů